2021
DOI: 10.24127/ajpm.v10i1.2812
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Problem Based Learning Terhadap Kemampuan Pemecahan Masalah Matematis Ditinjau Dari Gender Dan Level Sekolah

Abstract: Penelitian ini bertujuan untuk mengetahui perberdaan kemampuan pemecahan masalah matematis peserta didik yang memperoleh pembelajaran model Problem Based Learning (PBL) dengan siswa yang menggunakan model pembelajaran konvensional yang ditinjau dari gender (laki-laki dan perempuan) dan level sekolah (tinggi, sedang, rendah) di MTsN Kabupaten Tanah Datar. Jenis peneltian adalah eksperimen dan desain penelitian yang digunakan Randomized Pretest-Posttest Control Group Design dengan variabel bebas model PBL dan ko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
2
7
0
1
Order By: Relevance
“…Several constructivist theories, namely Piaget with his cognitive theory, Vygotsky with the concept of the zone of proximal development, and Brunner, namely the theory of scaffolding, also strengthen this research. This is consistent with the findings of Yerizon (2021), Febrian and Delyana (2020), and Pandiangan (2020), which state that the PBL model's implementation can help students become better problemsolvers since it requires them to seek solutions, which can help students evaluate their problem-solving skills. They will also get problem-solving training, with the difficulties that are given during the learning process mirroring actual problems encountered in daily life.…”
Section: Discussionsupporting
confidence: 90%
“…Several constructivist theories, namely Piaget with his cognitive theory, Vygotsky with the concept of the zone of proximal development, and Brunner, namely the theory of scaffolding, also strengthen this research. This is consistent with the findings of Yerizon (2021), Febrian and Delyana (2020), and Pandiangan (2020), which state that the PBL model's implementation can help students become better problemsolvers since it requires them to seek solutions, which can help students evaluate their problem-solving skills. They will also get problem-solving training, with the difficulties that are given during the learning process mirroring actual problems encountered in daily life.…”
Section: Discussionsupporting
confidence: 90%
“…This result aligns with research (Akbar et al, 2020), which reveals that female students are more organized in problem-solving. Several other studies have also revealed that the problem-solving abilities of female students are better than male students (Nurfitri & Jusra, 2021;Tunnajach & Gunawan, 2021;Yerizon et al, 2021). Male students tend to be lazy to write down information on the problems given and prefer to act directly according to their reasoning and understanding of the problem.…”
Section: Researcher : "Why Did You Work On This Problem the Same Numb...mentioning
confidence: 99%
“…The results of previous studies related to problem-solving show that female students have better problem-solving abilities than male students (Kusumaningsih et al, 2020;Nurfitri & Jusra, 2021;Tunnajach & Gunawan, 2021;Yerizon et al, 2021). This happens because female students are more thorough and structured in solving problems (Kusumaningsih et al, 2020;Subekti & Krisdiani, 2021).…”
Section: Introductionmentioning
confidence: 97%
“…The purpose of implementing a learning model or strategy is to create a learning climate with certain conditions to assist the learning process in order to create effective, efficient and attractive learning conditions (Yerizon et al, 2021). This problem-solving ability is needed so that students are able to compete globally in this century (Dewi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%